Research Problems on Popular, Social or Solidarity Economy. Transdiscipline in an complex objetc - Serra, Hugo Rodrigo (Universidad Nacional de Villa María, 2017)
This work arises as a response to the concerns about problems to approach the "Popular Economy" as an object of study in Social Sciences research. The popular, social or solidarity economy is a transdisciplinary object that takes categories of several social disciplines that approach similar problems, but that in no case can be confused. Thus, problems occur at the moment of operationalizing theoretical concepts insofar as concepts such as reproduction, capital and subject have different meanings both in theories different from the same disciplinary field as in different disciplines. We will try to problematize this question by addressing two underlying assumptions of transdisciplinary objects: the problems of commensurability and translatability between theories, and the question of whether or not there is a differentiation of discipline for Marxism.